Orlando Oliveros: The memory machine. Stories and conversations about the life, work and legacy of Gabriel García Márquez. Cartagena de Indias, Colombia: Gabo Foundation - López-González, Rosendo; Ramírez-Valencia, Astrid (Visión electrónica, 2022)
Orlando Oliveros: The memory machine. Stories and conversations about the life, work and legacy of Gabriel García Márquez